2013
DOI: 10.1093/aje/kws456
|View full text |Cite
|
Sign up to set email alerts
|

Professional Fighters Brain Health Study: Rationale and Methods

Abstract: Repetitive head trauma is a risk factor for Alzheimer's disease and is the primary cause of chronic traumatic encephalopathy. However, little is known about the natural history of, and risk factors for, chronic traumatic encephalopathy or about means of early detection and intervention. The Professional Fighters Brain Health Study is a longitudinal study of active professional fighters (boxers and mixed martial artists), retired professional fighters, and controls matched for age and level of education. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 25 publications
0
66
1
1
Order By: Relevance
“…10,[18][19][20][21][22] Early results from the Professional Fighters Brain Health Study, a 5-year longitudinal study of boxers and mixed martial arts fighters, who experienced repetitive subconcussive injuries as well as concussions, indicate that earlier age of first exposure to competitive boxing correlates with greater loss of caudate volume and greater axonal damage in the frontal lobe. 23,24 The young brain also has features that contribute to its resilience. Increased neuroplasticity in this age group has been shown to contribute to better outcomes after focal injuries.…”
Section: Susceptibility and Resilience Of Young Brainsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[18][19][20][21][22] Early results from the Professional Fighters Brain Health Study, a 5-year longitudinal study of boxers and mixed martial arts fighters, who experienced repetitive subconcussive injuries as well as concussions, indicate that earlier age of first exposure to competitive boxing correlates with greater loss of caudate volume and greater axonal damage in the frontal lobe. 23,24 The young brain also has features that contribute to its resilience. Increased neuroplasticity in this age group has been shown to contribute to better outcomes after focal injuries.…”
Section: Susceptibility and Resilience Of Young Brainsmentioning
confidence: 99%
“…Similar to a 'pitch count' in baseball, this concept has also recently been proposed for boxers. 24 No evidence is currently available to show a causal link between repetitive subconcussive 67 although the relationship between mTBI and PD risk remains uncertain. 68 In paediatric populations, particularly young athletes, the effects of single or repetitive concussions on the risk of later-life neurodegeneration and dementia are unknown.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…7 Briefly, professional fighters with a history of either boxing or mixed martial arts fighting were recruited in two cohorts, active and retired. Once screened for their appropriateness for the study, including ability and willingness to undergo an MRI, they were consented and underwent a visit including a structured interview on demographics and fight exposure, cognitive testing using central nervous system (CNS) vital signs, blood draw for genetic analysis, and MRI scan including anatomical and functional images.…”
Section: Methodsmentioning
confidence: 99%
“…Further, correlations existed between these regions and cognitive ability, suggesting a functional impact of the anatomic-fight exposure relationship. 6,7 More recently, we started to collect genetic data on participants. We tested the hypothesis that previously revealed that relationships would be moderated by e4 status.…”
Section: Introductionmentioning
confidence: 99%
“…This sport has grown and expanded immensely, attracting media, spectators and sponsors, and increased participants in specialized martial arts academies (Sheridan, 2010). This MMA phenomenon has drawn the attention of researchers from different fields, such as medicine (Bernick, et al, 2013), sociology (Spencer, 2014), motor behavior (Baker & Schorer, 2013), and sports training (Del Vecchio & Ferreira, 2013).…”
Section: Introductionmentioning
confidence: 99%